2021
DOI: 10.1177/10547738211051565
|View full text |Cite
|
Sign up to set email alerts
|

The Most Commonly Determined Nursing Diagnoses According to NANDA-I Taxonomy and Difficulties Using the Nursing Process in COVID-19 Outbreak

Abstract: The study was planned to determine the most common nursing diagnoses according to NANDA International (NANDA-I) taxonomy and difficulties experienced in using of nursing process in COVID-19 outbreak. The sample of the descriptive cross-sectional study consisted of nurses cared for patients with COVID-19 ( n = 114). Average age of nurses is 26.86 ± 6.68. Commonly determined nursing diagnoses according to NANDA-I taxonomy in patients with COVID-19 were imbalanced nutrition (66.7%), impaired gas exchange (40.4%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
(11 reference statements)
0
5
0
4
Order By: Relevance
“…Fonte: Autores (2022). Dados extraído da NANDA-I, (2018); Silva, et al, (2021); Arias, (2021); Laurindo et al, (2021); Barioni et al, (2022); Buffon et al, (2022); Azevedo et al, (2022); Tosun et al, (2022); Cussó et al, (2022); Aguña et al, (2021ª); Aguña et al, (2021b).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Fonte: Autores (2022). Dados extraído da NANDA-I, (2018); Silva, et al, (2021); Arias, (2021); Laurindo et al, (2021); Barioni et al, (2022); Buffon et al, (2022); Azevedo et al, (2022); Tosun et al, (2022); Cussó et al, (2022); Aguña et al, (2021ª); Aguña et al, (2021b).…”
Section: Resultsunclassified
“…O Quadro 3 Refere-se aos diagnósticos de enfermagem mais prevalentes para pacientes críticos com COVID-19, em UTI, de acordo com a revisão integrativa de literatura. Buffon et al, (2022); Azevedo et al, (2022); Tosun et al, (2022); Cussó et al, (2022); Aguña et al, (2021a); Aguña et al, (2021b).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Kalisch et al mentioned that the element of the nursing process is part of MNC ( 12 ). The results of Tosun et al showed that some nurses using the nursing process during the COVID-19 process had difficulties with it and often had difficulty in implementing care programs ( 48 ). In Labrague's study, interventions that required planning were more often missed ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…With education and experience rooted in the nursing process, the CNS also equipped the RPM nursing team with nursing diagnoses and nursing interventions to help patients care for themselves at home. For patients with COVID-19, the most frequently used examples include imbalanced nutrition, impaired gas exchange, acute confusion, and hopelessness 26 . Examples of nursing interventions the CNS emphasized for the direct care nursing team included adequate hydration and electrolyte replacement, coughing and deep breathing, use of expectorants, cooling compresses, education on the appropriate use of antipyretics and over-the-counter antidiarrheal agents, fall risk interventions, and active listening and anxiety management.…”
Section: Vn Practice Modelsmentioning
confidence: 99%